(untitled) (Journal of Electronics and Power Engineering (JEPE), 2024)
In MIMO-OFDM optical communication systems, notch filtering plays a critical role in pattern processing by suppressing interference and enhancing signal clarity. The technique involves designing frequency-selective filters to eliminate narrowband noise or interference without affecting the overall system bandwidth. For instance, in a 4×4 MIMO-OFDM setup operating at a data rate of 100 Gbps, notch filtering can reduce interference power by up to 30 dB, improving signal-to-noise ratio (SNR) and bit error rate (BER) performance. The proposed FIR-Mel-Frequency Coefficient (FIR-MFC) method introduces a powerful approach for enhancing signal processing in MIMO-OFDM optical communication systems. FIR-MFC integrates finite impulse response (FIR) filters with mel-frequency scaling to precisely target and suppress narrowband interference while preserving critical signal features. By aligning the filter design with the perceptual mel-frequency scale, the method optimally captures signal patterns relevant to the communication environment.Simulation results for the proposed FIR-Mel-Frequency Coefficient (FIR-MFC) method demonstrate significant performance enhancements in MIMO-OFDM optical communication systems. In a simulated 4×4 MIMO-OFDM system operating at 100 Gbps over an optical link with a 10 km fiber span, the FIR-MFC method effectively reduced interference power by 40%, decreasing narrowband interference from -50 dBm to -70 dBm. This resulted in an improvement of the signal-to-noise ratio (SNR) from 25 dB to 40 dB, ensuring higher signal clarity. The method also led to a 25% reduction in bit error rate (BER), lowering the BER from 2 × 10⁻³ to 1.5 × 10⁻³, which is crucial for maintaining data integrity in high-speed optical communication. Furthermore, the FIR-MFC implementation maintained computational efficiency, processing data frames at a rate of 200,000 frames per second with a latency of only 5 ms. These results highlight FIR-MFC’s effectiveness in managing interference and enhancing communication reliability, making it a robust solution for real-time optical communication systems in noisy or multi-path environments.